Antimicrobial Activity and Cytoxicity of Several Sumbawa Traditional Oils (Minyak Sumbawa) in Sumbawa Regency, West Nusa Tenggara, Indonesia - Rimbun Anggih Chaidir Riri; Manguntungi Baso; Zaenal Mustopa Apon; Islam Izzul; Hussain Zahid; Iqrar Irum (E3S Web of Conferences, 2023)
Sumbawa oil or Minyak Sumbawa, is one of Indonesia’s original traditional oils used for more than just external applications and is believed to treat various diseases, from body aches and stomach infections to post-surgery treatment. However, there still needs to be more research that scientifically discusses its medicinal effects. This study evaluates the antimicrobial properties and cytotoxicity of several locally made Minyak Sumbawa in Sumbawa Regency, West Nusa Tenggara, Indonesia. Minyak Sumbawa from Batu Lanteh (BTL) showed the highest antimicrobial properties against Salmonella thypi, Listeria monocytogenes, Escherichia coli, Staphylococcus aureus compared to those from Lunyuk (LNK), Pernek (PRN), Taliwang (TLW), Utan (UTN) and from Sumbawa Besar (SBW). In contrast, Minyak Sumbawa from Labuan Badas (BDS) has the highest activity against Staphylococcus epidermidis. Using the BSLT method, all samples showed low toxicity. The result showed that Minyak Sumbawa has various activities against gram-positive and negative bacteria and is safe for consumption overall. Since the oils were made with different recipes, therefore it will affect its chemical constituent. On the other hand, Minyak Sumbawa can be modified accordingly for specific health benefits by adjusting and standardizing the recipe to improve the quality of Indonesian traditional medicine.